The Effectiveness of a Combination of Lavender Aromatherapy and Sleep Hygiene in Improving Sleep Quality in Patients with Diabetes Mellitus: A Quasi Experimental Study - Yuli Widyastuti; Fitrian Rayasari; Dewi Anggareni; Wati Jumaiyah; Ita Indraswati (Jurnal Berita Ilmu Keperawatan)
Type 2 diabetes mellitus (T2DM) is often accompanied by sleep disturbances that can worsen glycemic control and increase the risk of complications. The combination of lavender aromatherapy and sleep hygiene is a non-pharmacological intervention that can potentially improve sleep quality in T2DM patients. This study aims to evaluate the effectiveness of lavender aromatherapy and sleep hygiene in improving sleep quality in T2DM patients. The study used a quasi-experimental design with a pre-test and post-test approach. The sample consisted of 15 inpatients with T2DM at PKU Muhammadiyah Gamping Hospital, who were selected using an accidental sampling method. Interventions included lavender aromatherapy inhalation and sleep hygiene implementation, including ablution, prayer, sleeping position, and lighting. Data were analyzed using paired t-tests to see changes in Pittsburgh Sleep Quality Index (PSQI) scores before and after the intervention. The mean PSQI score of the patients decreased significantly from 8.67 before the intervention to 5.40 after the intervention (p=0.001), indicating a significant improvement in sleep quality. The combination of lavender aromatherapy and sleep hygiene effectively improves sleep quality in T2DM patients. This intervention can be adopted in nursing practice to manage sleep disorders holistically.